Nonlinear Optics Applications - Karpierz, Miroslaw A.; Assanto, Gaetano (Photonics Letters of Poland, 2012)
A brief editorial overview of works devoted to nonlinear optics in the current issue is presented. Full Text: PDF References M.A.Karpierz and G.I. Stegeman, "Nonlinear Optics: A Vibrant Field", Photon. Lett. Poland 1, 145-147 (2009) [CrossRef]